2023
DOI: 10.1002/ange.202306631
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of Molybdenum Complexes Bearing PNP‐Type Pincer Ligand toward Ammonia Formation

Abstract: We newly designed and prepared a novel molybdenum complex bearing a 4‐[3,5‐bis(trifluoromethyl)phenyl]pyridine‐based PNP‐type pincer ligand, based on the bond dissociation free energies (BDFEs) of the N−H bonds in molybdenum‐imide complexes bearing various substituted pyridine‐based PNP‐type pincer ligands. The complex worked as an excellent catalyst toward ammonia formation from the reaction of an atmospheric pressure of dinitrogen with samarium diiodide as a reductant and water as a proton source under ambie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…61 Structures like 2 di (one bridging N 2 moiety) are well known for example from the many Mo-NN-Mo complexes introduced by the Nishibayashi group. 29,30 Assessing the feasibility of dimerization, we studied both tungsten and molybdenum pincer complexes, featuring ligands L1, L10, and L11. Gratifyingly, the formation of 1 di proved to be highly unlikely for all tungsten/molybdenum pincer complexes, with energy ranging from 44.5 to 56.7 kcal mol −1 (Fig.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
See 2 more Smart Citations
“…61 Structures like 2 di (one bridging N 2 moiety) are well known for example from the many Mo-NN-Mo complexes introduced by the Nishibayashi group. 29,30 Assessing the feasibility of dimerization, we studied both tungsten and molybdenum pincer complexes, featuring ligands L1, L10, and L11. Gratifyingly, the formation of 1 di proved to be highly unlikely for all tungsten/molybdenum pincer complexes, with energy ranging from 44.5 to 56.7 kcal mol −1 (Fig.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…[22][23][24][25] The most recent and impressive developments in catalytic ammonia formation using N 2 /H + /e − were achieved mainly by the groups of Nishibayashi, Nishibayashi/Yoshizawa and Peters. [26][27][28][29][30] With regard to the N 2 /H 2 reaction system, Schneider, Holthausen, and co-workers 31 have observed that the nitrogen center of molecular ruthenium pincer nitrides, which are potentially engaged in an N 2 /H 2 catalytic cycle, can undergo conversion into NH 3 upon exposure to H 2 . Notably, Hou et al 32 revealed the potential of trinuclear titanium hydrides in breaking the NuN triple bond in the presence of H 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been extensively used as environmental remediation materials because of their exceptional performance in photocatalysis. Molybdenum oxides have garnered significant attention in recent times for their potential applications in several domains, such as humidity sensors, magnetic fields, the microwave approach, optical fibers, scintillator materials, photoluminescence devices, catalysis, and electrochemical sensors, owing to their physiochemical characteristics [18][19][20][21]. Adding certain precious metals to the oxides can enhance their optical, catalytic, and sensing properties.…”
Section: Introductionmentioning
confidence: 99%